PWE-112 Characterising barium swallow dysmotility?– are they always significant?. (17th June 2017) - Koo, S; Davidson, A; Bray, A; Lim, YC
Abstract : Introduction: Although high resolution oesophageal manometry (HROM) is the gold standard for evaluating oesophageal dysmotility, barium swallow (BS) is widely available and is commonly used. In this study we aim to correlate barium swallow reported oesophageal dysmotility to HROM results. Method: We reviewed paired results of BS and HROM from a retrospective registry in our hospital from 2014 to 2016. We excluded patients who have had previous oesophageal surgery for achalasia or reflux, biopsy proven eosinophilic oesophagitis and failed HROM examination. BS results were correlated to HROM findings as per the Chicago Classification of Oesophageal Motility Disorder 2012 and 2015 guidelines, depending on when the studies were performed. Sensitivity and specificity for significant HROM findings were assessed. Results: 95 cases were analysed. The main indications were reflux symptoms (50.5%) and dysphagia (32.6%). Results are summarised in Table 1. 60 cases of BS were reported with abnormal oesophageal motility of which 11 cases (11.6%) were described as achalasia and these were confirmed on HROM (achalasia- 10, OGJ outflow obstruction- 1). 49 cases were reported with non-specific dysmotility on BS (tertiary contractions, food bolus only clearing with fluid, or slow transit of food bolus). Of these, 12 (24.5%) cases were significant (achalasia-1, OGJ outflow obstruction-3, hypercontractile oesophagus-3, distal oesophageal spasm-1, absent peristalsis-4). 21 cases (42.9%) had peristaltic abnormality (nutcracker oesophagus-2, weak peristalsis-19) and the remaining 16 cases (32.7%) had normal HROM. 35 cases had a normal BS, of which 2 (5.71%) had absent peristalsis on HROM. 15 (42.9%) had peristaltic abnormalities (weak peristalsis) and 18 (51.4%) had normal HROM. There were no cases of achalasia in this group. In total only 38.3% (23/60) of BS reported dysmotility corresponds to a significant abnormality on the HROM. Conversely, 5.71% of normal BS corresponded to a significant abnormality in HROM. This confers BS with a sensitivity of a 92.0% and specificity of 47.1% in detecting significant abnormality on HROM. Conclusion: Barium swallow identifies achalasia but is less specific for other recognised oesophageal dysmotility disorder which may be clinically important. Barium swallow reported dysmotility can be considered for further characterisation with HROM. Disclosure of Interest: None Declared